2016
DOI: 10.3389/fpls.2016.01736
|View full text |Cite|
|
Sign up to set email alerts
|

Expression Level of the DREB2-Type Gene, Identified with Amplifluor SNP Markers, Correlates with Performance, and Tolerance to Dehydration in Bread Wheat Cultivars from Northern Kazakhstan

Abstract: A panel of 89 local commercial cultivars of bread wheat was tested in field trials in the dry conditions of Northern Kazakhstan. Two distinct groups of cultivars (six cultivars in each group), which had the highest and the lowest grain yield under drought were selected for further experiments. A dehydration test conducted on detached leaves indicated a strong association between rates of water loss in plants from the first group with highest grain yield production in the dry environment relative to the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 44 publications
(65 reference statements)
2
44
0
Order By: Relevance
“…Amplifluor-like SNP analysis, as described earlier (Shavrukov et al 2016;Jatayev et al 2017), was carried out using a QuantStudio-7 Real-Time PCR Cycler (ThermoFisher Scientific, USA).…”
Section: Snp Amplifluor-like Genotyping Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…Amplifluor-like SNP analysis, as described earlier (Shavrukov et al 2016;Jatayev et al 2017), was carried out using a QuantStudio-7 Real-Time PCR Cycler (ThermoFisher Scientific, USA).…”
Section: Snp Amplifluor-like Genotyping Assaymentioning
confidence: 99%
“…Manuscript to be reviewed PCR cycling followed a program adjusted from those published earlier (Shavrukov et al 2016;Jatayev et al 2017), and included initial denaturation at 95 C for min; 26-28 cycles of C for 30 s, 55 0 C for s, and 0 C for 50 s; and final extension at 72 0 C for 5 min. Genotyping with SNP calling was determined automatically by software accompanying the instrument, but each SNP result was checked manually using amplification curves and allele discrimination.…”
Section: Snp Amplifluor-like Genotyping Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Drought Responsive Element Binding ( DREB ) genes have been reported as regulatory components of abiotic stress responses and, particularly, drought response ( Zhu, 2002 ; Agarwal and Jha, 2010 ; Fujita et al, 2011 ; Kuromori et al, 2014 ; Rehman and Mahmood, 2015 ; Sah et al, 2016 ; Verma et al, 2016 ; Agarwal et al, 2017 ). Recently, we identified that expression levels of the TaDREB5 gene, which belongs to the DREB2 -type TFs, correlate with yields of wheat varieties grown in the dry conditions of Kazakhstan ( Shavrukov et al, 2016 ). Application of the Amplifluor-like SNP marker KATU-48, developed in our laboratory, showed a genetic polymorphism associated with two groups of Kazakh wheat genotypes.…”
Section: Introductionmentioning
confidence: 99%